Segregation and Wellbeing of Third-generation Migrants in Akpabuyo, Nigeria - F. E. Ojong; G. E. Odika; J. O. Emeka; E. O. Effiom; A. M. O. Agba; P. U. Festus; Pius U. Angioha; Abayomi I. Akintola; Tabe E. Ojong (PT Mattawang Mediatama Solution, 2023)
The situation associated with migrant population in any society is not devoid of challenges and is most time tainted with ethnic sentiment and social exclusion. Therefore, this study examined the effect of segregation on the wellbeing of third-generation migrants in Akpabuyo Local Government Area of Cross River State, Nigeria. Specifically, it investigated the upshot of employment, socio-political and economic exclusion on the wellbeing of third-generation migrants. Multi-stage sampling technique was adopted in selecting the sample for the study. A structured questionnaire was used to elicit information from 331 respondents. Pearson Product Moment Correlation Coefficient at 0.05 level of significance was used for data analysis. Findings revealed that socio-political, employment and economic marginalization of third-generation migrants negatively affect their wellbeing. Importantly, it accounts for the high level of unemployment and drug addiction, poor access to education and health, low level of income, high crime rate and lack of basic social amenities among third-generation migrants in Akpabuyo, Nigeria. The study recommends that government at all levels should adopt a comprehensive and inclusive policy that would ensure the highest possible level of equality, assimilation, and social cohesion among migrants and indigenous population.